Amidoxime modified Fe3O4@TiO2 particles for antibacterial and efficient uranium extraction from seawater. (January 2022) - Li, Nan; Gao, Pin; Chen, Huawei; Li, Fulin; Wang, Zhining
Abstract: Uranium extraction and recovery play a critical role in guaranteeing the sustainable nuclear energy supply and protecting the environmental safety. The ideal uranium sorbents possess high adsorption capacity, excellent selectivity and reusability, as well as outstanding antimicrobial property, which are greatly desired for the real application of uranium extraction from seawater. To address this challenge, a novel magnetic core-shell adsorbent was designed and fabricated by a facile method. The obtained amidoximed Fe3 O4 @TiO2 particles (Fe3 O4 @TiO2 -AO) achieved equilibrium in 2 h and the maximum adsorption capacity calculated from Langmuir model is 217.0 mg/g. The adsorption kinetics followed the pseudo-second-order model. Meanwhile, the Fe3 O4 @TiO2 -AO exhibited great selectivity when competitive metal ions and anions coexisted. In addition, the magnetic Fe3 O4 @TiO2 -AO could be conveniently separated and collected by an external magnetic field, the regeneration efficiency maintained at 78.5% even after ten adsorption-desorption cycles. In natural seawater, the uranium uptake reached 87.5 μg/g in 33 days. Furthermore, the TiO2 contained adsorbent showed effective photo induced bactericidal properties against both E. coli and S. aureus . The Fe3 O4 @TiO2 -AO with great U(VI) adsorption performance is highly promising in uranium extraction and reclamation. Graphical abstract: Image 1 Highlights: Photoinduced antimicrobial Fe3 O4 @TiO2 -AO is prepared. Fe3 O4 @TiO2 -AO can selectively and efficiently adsorb and separate uranium (VI). Fe3 O4 @TiO2 -AO has high reusability and outstanding stability. Fe3 O4 @TiO2 -AO has good uranium adsorption performance in natural seawater. Fe3 O4 @TiO2 -AO showed effective photo induced bactericidal properties.